Histological Investigation of Fetal, Adullt and Senil Rat Thymus Glands - Koyutürk, Leyla Canpolat (Fırat University, 2002)
Aim: In order to identify subtle changes in thymus cell morphology during development was histologically examined thymus glands at different stages. Material and Method: Thymus tissues of 14, 15, 16, 17, 18, 19 daily fetus, 6 montly adult, 1 years old senil rats the materials of this study have been investigated. Tissues fixed with 10 % formaldehyde. 5m m thicked paraffin sections were stained by Heamatoxilen and Eosine. Results: 14 day old fetuses, trabecular structures which extend from the capsule had distincted into the lobulles to thymus. The connective tissue septa of the thymus had developed. In the 14 th -15. days, cortico-medullar junction was discriminated. In that days, the vascularization of thymus had been beginned. In the16-18. days, were seen well organized to structuraly discriminated of the medulla from cortex . In the 19. day, the Hassall corpusculles had been beginned to develop in the medulla. In adults, Hassall corpuscules observed large number in the medulla. Thymocytes into structure of cortex were more basophilic and more density which they were done essential structure of cortex. In the thymus of rat in the one year age, was dramatically exhibited tissue changes. In particularly, were observed reduction in the number of the thymocytes and in the areas interlobulles and intralobulles have been increased adipose tissue (fatty infiltration). Conclusion: In conclusion, thymus is remodelling, with time. Thymus involution is not only a simple shrinkage of the organ, is result of a series of the mechanismal process among different cells.

Amaç: Gelişim esnasında, timus hücre morfolojisindeki ince değişiklikleri tayin etmek için farklı dönemlerdeki timus bezleri histolojik olarak incelendi. Materyal ve Method: Çalışmanın materyallerini 14, 15, 16, 17, 18, 19 günlük fötüs ve 6 aylık ergin ve 1 yaşındaki ergin sıçan timus dokusu oluşturmaktadır. Dokular % 10'luk formalinle tesbit edildiler. 5 µm kalınlığındaki parafin kesitler Hematoksilen ve Eozin'le boyandı. Bulgular: 14 günlük fötüslerde, kapsülden çıkan trabeküler yapılar, timusu lobüllere ayırmıştı. Lobülleri ayıran bağ dokusu septası gelişmişti. 14-15. Günlerde, kortikomedüller sınır ayıtdediliyordu. Bu günlerde, timusun vaskularize oluşu dikkat çekiciydi.16-18. Günlerde, medüllanın korteksten yapısal ayrımı yapılmaktaydı. 19. Günde, Hassall korpüskülleri medüllada gelişmeye başlamıştı. Erginde, çok sayıda medüllada Hassall korpüsküleri gözlendi. Korteks'te yer alan timositler daha bazofilik ve daha yoğun olup, korteksin esas yapısını oluşturuyordu. Bir yaşındaki sıçan timuslarında, doku değişiklikleri dramatik olarak gözleniyordu. Timosit yoğunluğunda azalma, lobülüsler arası ve lobüllerde yağ dokusunun (yağ infiltrasyonu) artışı barizdi. Sonuç: Sonuçta timus zamanla yeniden şekillenir. Timus involüsyonu organın basit bir büzülmesi değildir, farklı hücreler arasındaki mekanizmal olayların bir serisinin sonucudur.
FÖTÜS, ERGİN, YAŞLI SIÇAN TİMUS BEZİNİN HİSTOLOJİK İNCELENMESİ